Pengaruh Struktur Kepemilikan dan Komisaris Independen terhadap Prediksi Financial Distress - Aisyah Aisyah; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2022)
This research aims to analyze the effect managerial ownership, institutional ownership and independent commissioners on financial distress. This research uses a quantitative approach with a causal associative research type. The data used in this study are annual reports of sector basic and chemical industry companies listed on the Indonesia Stock Exchange in 2016-2020. Using a purposive sampling method we obtained 150 samples from 30 companies conducting observations from 2016 – 2020. This research uses multiple linear regression analysis for hypothesis testing. The result showed that the managerial ownership has a negative and significant effect on financial distress and institutional ownership has a positive and significant effect on financial distress. While independent commissioners have no significant effect on financial distress.